2003
DOI: 10.1093/ajcn/77.3.731
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical activity in healthy children is associated with fat mass

Abstract: Although direct effects of UFF and UFE on body composition were not shown, our findings strongly suggest that a higher adrenocortical activity is one endocrine-metabolic feature of healthy children with higher body fat. Whether urinary GC is a long-term predictor of fat gain during childhood should be analyzed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 30 publications
1
65
1
Order By: Relevance
“…51 In the present study, we compared 11b-HSD1 and leptin expression levels in SC and OM between female and male subjects both in children and adults and did not find any significant differences between genders. There was no significant change in 11b-HSD1 expression with age (o6 years of age vs X6 years of age), when girls and boys were analyzed separately.…”
Section: Discussionmentioning
confidence: 60%
“…51 In the present study, we compared 11b-HSD1 and leptin expression levels in SC and OM between female and male subjects both in children and adults and did not find any significant differences between genders. There was no significant change in 11b-HSD1 expression with age (o6 years of age vs X6 years of age), when girls and boys were analyzed separately.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, Dimitriou et al (35) reported in pre-pubertal and pubertal healthy children with normal BMI a strong correlation between age and the sum of urinary cortisol tetrahydro metabolites (THECTHFCaTHF). In their study, the (THFC5a-THF)/THE ratio decreased with age into puberty in healthy girls and boys with a normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…18 Although the relationships between stress-related cortisol secretion and markers of the metabolic syndrome have been demonstrated in adults, [21][22][23][24][25] little evidence is available in children. 26 Likewise, few studies have examined the relationship between physical activity and stress-related variables (ie, perceived stress, anxiety, depression, self-esteem, etc) in children and adolescents. In general, an inverse relationship has been demonstrated between physical activity and stress-related measures.…”
mentioning
confidence: 99%